A high-resolution spectroscopic search for multiple populations in the 2 Gyr old cluster NGC 1846. Issue 1 (5th December 2022) - Oh, W S; Nordlander, T; Da Costa, G S; Mackey, A D
ABSTRACT: We present detailed C, O, Na, Mg, Si, Ca, Ti, V, Fe, Zr, Ba, and Eu abundance measurements for 20 red giant branch (RGB) stars in the Large Magellanic Cloud (LMC) star cluster NGC 1846 ([Fe/H] = −0.59). This cluster is 1.95 Gyr old and lies just below the supposed lower age limit (2 Gyr) for the presence of multiple populations in massive star clusters. Our measurements are based on high- and low-resolution VLT/FLAMES spectra combined with photometric data from Hubble Space Telescope (HST). Corrections for non-local thermodynamic equilibrium effects are also included for O, Na, Mg, Si, Ca, Fe, and Ba. Our results show that there is no evidence for multiple populations in this cluster based on the lack of any intrinsic star-to-star spread in the abundances of Na and O: We place 95  per cent confidence limits on the intrinsic dispersion for these elements of ≤0.07 and ≤0.09 dex, respectively. However, we do detect a significant spread in the carbon abundances, indicating varying evolutionary mixing occurring on the RGB that increases with luminosity. Overall, the general abundance patterns for NGC 1846 are similar to those seen in previous studies of intermediate-age LMC star clusters and field stars.